Harmonic Reduction Comparison In Multilevel Inverters For Industrial Application - Zulkifilie , Ibrahim (JATIT & LLS, 2016)

(untitled)
This paper presents the simulation studies adapters’ type of multi-level consists of H-bridge cascade imposed to reduce harmonic for high power applications.Applications of multilevel converters are able to reduce the number of harmonics contained in the system of low-voltage electrical distribution.This study deals with a comparative analysis between the three stages of imposed multilevel inverter circuits cascaded H-bridge inverter with sinusoidal pulse width modulation (SPWM) strategies.Used five to nine levels SPWM inverter with the functions of the switching of the principles of mitigation of harmonic components of the output voltage of the multilevel converters operation.The simulation results show that the total harmonic distortion of the effort (THDV) adapters for multiple outputs levels and decreased both realized on the basis of the content of the low standard IEC.